Wzór społeczny w koncepcji socjologicznej Tadeusza Szczurkiewicza - Nocuń-Jankowska, Maria (Wydział Prawa i Administracji UAM, 1985)
The article is drawing attention to the cognitive weight of the Tadeusz Szczurkiewiczem concept of social pattern. Contrary to other sociologists the author is reducung the social pattern neither to descriptive-typological instrument, nor to a device illustrating particular types of behavior, nor to a model postulate to be followed. The social pattern is understood normatively by Tadeusz Szczurkiewicz and its origins lie in the fact of social co-existence approached against the bacground of the social group. Thus the existence of the group is the prerequisite to the existence and study of social patterns.
Social pattern in the sociological concept of Tadeusz Szczurkiewicz